Resin composition
By combining components such as the first resin, the second resin and the crosslinking agent in the resin substrate, the shortcomings of the low dielectric resin in the glass transfer temperature and fluidity are solved, and the glass is improved under the low dielectric electrical specifications are achieved. The effect of transferring temperature and fluidity improves processability.
Patent Information
- Application Number
- CN202310911441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-14
- Filing Date
- 2023-07-24
- Publication Date
- 2024-12-17
AI Technical Summary
When existing low-dielectric resins reduce the dielectric constant and loss factor, the glass transfer temperature is low and the fluidity is poor, resulting in a decrease in processability and it is difficult to meet the needs of high-frequency and rapid transmission.
The resin substrate is combined with the first resin and the second resin, and divinylbenzene crosslinking agent, halogen-free flame-resistant agent and spherical silica are added, and styrene, divinylbenzene and ethylene monomers are mixed, and bismaleyl is bismaleyl. A combination of imine modified polyphenylene ether resin combined with silicone coupling agent optimizes the electrical properties and fluidity of the resin.
While maintaining low dielectric electrical specifications, the glass transfer temperature and fluidity are improved, the overall processability is improved, and the performance of resin composition is achieved.
Smart Images

Figure BDA0004355690240000041 
Figure BDA0004355690240000051 
Figure BDA0004355690240000061
Abstract
Description
Technical Field
[0001] The present invention relates to a resin, and in particular to a low dielectric resin composition. Background Art
[0002] In recent years, with the development of 5G communications, copper-clad laminate materials have been developed towards the goal of lower dielectric (low-k) properties. The current dielectric constant (Dk) of the substrate is about 3.2 to 5.0, which is not conducive to future high-frequency and fast transmission applications. In the current low-dielectric formula, a certain proportion of a new low-dielectric resin (Poly-DVB, the first resin below) can be added to reduce the electrical properties to a dissipation factor (Df) less than 0.0015. However, while achieving low electrical specifications, it may be accompanied by a low glass transition temperature (Tg) and / or poor fluidity, resulting in a decrease in overall processability.
[0003] Therefore, developing a resin composition that can increase the glass transition temperature and / or improve fluidity while maintaining low dielectric properties to achieve good processability of the resin composition is an urgent goal for the industry. Summary of the invention
[0004] The present invention is directed to a resin composition which has the effect of increasing the glass transition temperature while maintaining low dielectric electrical specifications.
[0005] According to an embodiment of the present invention, the resin composition includes a resin base, a halogen-free flame retardant, spherical silica and a siloxane coupling agent. The resin base includes a first resin, a second resin and a divinylbenzene crosslinking agent. The first resin is polymerized from a first monomer mixture including styrene, divinylbenzene and ethylene. The second resin includes a polyphenylene ether resin modified by bismaleimide.
[0006] In the resin composition according to an embodiment of the present invention, based on 100 parts by weight of the above-mentioned resin base, the content of the first resin is 30 parts by weight to 60 parts by weight, the content of the second resin is 20 parts by weight to 40 parts by weight, and the content of the divinylbenzene crosslinking agent is 10 parts by weight to 30 parts by weight.
[0007] In the resin composition according to the embodiment of the present invention, based on 100 parts by weight of the above-mentioned resin base, the added amount of the halogen-free flame retardant is 20 phr to 50 phr.
[0008] In the resin composition according to the embodiment of the present invention, based on 100 parts by weight of the total weight of the resin base and the halogen-free flame retardant, the amount of spherical silica added is 20 parts by weight to 50 parts by weight.
[0009] In the first monomer mixture according to an embodiment of the present invention, the molar ratio of styrene:divinylbenzene:ethylene is 1:1:1 to 2:2:1.
[0010] The resin substrate according to the embodiment of the present invention further includes SBS resin, which is polymerized from a second monomer mixture including styrene, 1,2-butadiene and 1,4-butadiene.
[0011] In the second monomer mixture according to an embodiment of the present invention, the molar ratio of styrene:1,2-butadiene:1,4-butadiene is 1:6:4 to 4:9:3.
[0012] In the resin composition according to the embodiment of the present invention, based on 100 parts by weight of the above-mentioned resin base, the content of the SBS resin is 0 parts by weight to 30 parts by weight.
[0013] In the resin composition according to the embodiment of the present invention, the weight average molecular weight of the SBS resin is 3500 to 5500.
[0014] In the resin composition according to the embodiment of the present invention, the spherical silica has a surface modification of acrylic or vinyl and has an average particle size of 2.0 μm to 3.0 μm.
[0015] In the resin composition according to the embodiment of the present invention, the electrical properties of the resin composition are a dielectric constant of 3.0 to 3.1 and a loss factor of less than 0.0015, and a heat resistance specification of a glass transition temperature greater than 210°C.
[0016] Based on the above, the resin composition of the present invention can have low dielectric properties through the combination of a first resin (formed by polymerization of a monomer mixture including styrene, divinylbenzene and ethylene) and a second resin (including a polyphenylene ether resin modified by bismaleimide). Furthermore, by introducing a cross-linking agent containing divinylbenzene, the low dielectric properties can be maintained, and at the same time, the glass transition temperature is increased and the fluidity is improved, thereby improving the overall processability. DETAILED DESCRIPTION
[0017] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are illustrative only, and the present invention is not limited thereto.
[0018] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as the arbitrary value and the smaller numerical range are written in the description text of the specification.
[0019] The resin composition of the present invention comprises a resin base, a halogen-free flame retardant, spherical silica and a siloxane coupling agent. The resin base comprises a first resin, a second resin and a crosslinking agent. The first resin is polymerized from a monomer mixture comprising styrene, divinylbenzene and ethylene. The second resin comprises a polyphenylene ether resin modified by bismaleimide. The crosslinking agent is divinylbenzene. The above-mentioned various components will be described in detail below.
[0020] Resin base
[0021] In the present invention, the resin base is a resin component in the resin composition, including a first resin, a second resin, an SBS resin, and a cross-linking agent for polymerizing the resins. The above components are described below.
[0022] [First resin]
[0023] In the present embodiment, the first resin may be polymerized from a first monomer mixture including styrene, divinyl benzene and ethylene. In the first monomer mixture, the molar ratio of styrene: divinyl benzene: ethylene is 1:1:1 to 2:2:1. That is, the first resin has a styrene ratio of 10% to 40%, a divinyl benzene ratio of 10% to 40%, and a vinyl ratio of 10% to 20%. In some embodiments, the number average molecular weight (Mn) of the first resin may be approximately 4500 to 6500. In some embodiments, based on 100 parts by weight of the resin base, the content of the first resin is, for example, 30 parts by weight to 60 parts by weight, preferably, for example, 35 parts by weight to 45 parts by weight. Adding the first resin to the resin composition can effectively reduce the dielectric constant (Dk) and dissipation factor (Df) of the resin composition to achieve low dielectric electrical specifications.
[0024] [Second resin]
[0025] In the present embodiment, the second resin may include a polyphenylene ether (PPE) resin modified with bismaleimide (BMI). For example, the second resin of the present invention may be a polyphenylene ether resin modified with bismaleimide (PPE-BMI) disclosed in Taiwan Patent Publication No. I774559, and the disclosure of Taiwan Patent Publication No. I774559 is incorporated herein by reference in its entirety.
[0026] For example, the chemical structure of the polyphenylene ether resin modified with bismaleimide can be represented by the following chemical formula:
[0027]
[0028] R may be, for example, a direct bond, a methylene group, an ethyl group, an isopropyl group, a 1-methylpropyl group, a sulfone group or a fluorene group, and n may be an integer between 3 and 25, preferably an integer between 10 and 18.
[0029] The polyphenylene oxide resin modified with bismaleimide can be formed by the manufacturing method disclosed in Taiwan Patent Publication No. 1774559, but the present invention is not limited thereto. The polyphenylene oxide resin modified with bismaleimide can also be formed by other suitable modification methods.
[0030] In some embodiments, based on 100 parts by weight of the resin base, the content of the second resin is, for example, 20 parts by weight to 40 parts by weight, preferably, for example, 30 parts by weight to 40 parts by weight, but not limited thereto. Since the chemical structure of the second resin has both a main chain of polyphenylene ether and a terminal modified by a highly heat-resistant reactive group (i.e., bismaleimide), the second resin has a relatively low dielectric constant and a relatively low loss factor.
[0031] [SBS resin]
[0032] In the present embodiment, the SBS resin refers to a styrene-butadiene-styrene block copolymer (SBS). The SBS resin may be polymerized from a second monomer mixture including styrene, 1,2-butadiene and 1,4-butadiene. In the second monomer mixture, the molar ratio of styrene:1,2-butadiene:1,4-butadiene may be 1:6:1 to 4:9:3. That is, the SBS resin has a styrene base ratio of 10% to 40%, a 1,2-butadiene base ratio of 60% to 90%, and a 1,4-butadiene base ratio of 10% to 30%. The weight average molecular weight (Mw) of the SBS resin is about 3500 to 5500. In some embodiments, based on 100 parts by weight of the resin base, the content of the SBS resin is, for example, 0 parts by weight to 30 parts by weight, but is not limited thereto. Adding SBS resin to the resin composition can improve the phase separation between resins, enhance fluidity and filling properties, and thus enhance overall processability while maintaining low dielectric properties.
[0033] [Crosslinking agent]
[0034] Crosslinking agents are used to increase the degree of crosslinking of thermosetting resins, adjust the rigidity and toughness of substrates, and adjust processability. Common crosslinking agents are, for example, 1,3,5-triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethallylisocyanurate (TMAIC), diallyl phthalate, divinylbenzene or 1,2,4-Triallyl trimellitate, etc., or a combination thereof. In the present invention, the crosslinking agent at least includes a divinylbenzene (DVB) crosslinking agent. In some embodiments, based on 100 parts by weight of the resin substrate, the content of the divinylbenzene crosslinking agent is, for example, 10 parts by weight to 40 parts by weight, preferably, for example, 10 parts by weight to 30 parts by weight. By introducing a divinylbenzene crosslinking agent into the resin composition, the electrical specification of low dielectric constant can be maintained, while the glass transition temperature can be increased and the resin fluidity can be improved, thereby improving the overall processability.
[0035] Halogen-free flame retardant
[0036] In this embodiment, specific examples of the halogen-free flame retardant can be phosphorus-based flame retardants, which can be selected from phosphate esters, such as triphenyl phosphate (TPP), resorcinol bisphosphate (RDP), bisphenol A di(diphenyl) phosphate (BPAPP), bisphenol A di(dimethyl) phosphate (BBC), resorcinol diphosphate (CR-733S), resorcinol-bis(di-2,6-dimethylphenyl phosphate) (PX-200); can be selected from phosphazenes, such as polydi(phenoxy)phosphazene (SPB-100); ammonium polyphosphate, melamine phosphate (MPP, i.e., Melamine Polyphosphate), melamine cyanurate; can be selected from one or more combinations of DOPO-based flame retardants, such as DOPO (such as structural formula C), DOPO-HQ (such as structural formula D), di-DOPO derivative structure (such as structural formula E), etc.; aluminum-containing hypophosphites (such as structural formula F). In some embodiments, based on 100 parts by weight of the resin base, the amount of the halogen-free flame retardant added is, for example, 20 phr to 50 phr.
[0037]
[0038]
[0039] Spherical silica
[0040] In this embodiment, the spherical silica is preferably prepared by a synthetic method to reduce electrical properties and maintain fluidity and filling properties. The spherical silica has a surface modification of acrylic or vinyl, a purity of about 99.0% or more, and an average particle size (D50) of about 2.0 microns to 3.0 microns. In some embodiments, the amount of spherical silica added is, for example, 20 parts by weight to 50 parts by weight based on 100 parts by weight of the total weight of the resin substrate and the halogen-free flame retardant.
[0041] Siloxane coupling agent
[0042] In this embodiment, the siloxane coupling agent may include but is not limited to siloxane compounds. In addition, according to the type of functional group, it can be divided into amino silane compounds, epoxy silane compounds, vinyl silane compounds, ester silane compounds, hydroxyl silane compounds, isocyanate silane compounds, methacryloxy silane compounds and acryloxy silane compounds. In some embodiments, the amount of the siloxane coupling agent added is, for example, 0.1 phr to 5 phr based on 100 parts by weight of the resin composition. By adding the siloxane coupling agent to the resin composition, the compatibility and crosslinking degree with the glass fiber cloth and powder can be enhanced.
[0043] additive
[0044] In addition to the above components, the resin composition of the present invention may further include other additives, such as peroxides initiators.
[0045] It should be noted that the resin composition of the present invention can be processed into a prepreg and / or a copper foil substrate (CCL) according to actual design requirements, so the prepreg and copper foil substrate made using the resin composition of the present invention also have better reliability (can maintain the required electrical properties). In some preferred embodiments, the dielectric constant of the substrate (or prepreg) made of the resin composition is about 3.0 to 3.1, the loss factor is less than about 0.0015, reaching the electrical specification of ultra-low dielectric, and can have a higher glass transition temperature, for example, greater than 210°C.
[0046] The resin composition of the present invention is described in detail below by way of examples. However, the following examples are not intended to limit the present invention.
[0047] Example
[0048] In order to prove that the resin composition proposed in the present invention can maintain a low dielectric constant and / or a low dissipation factor to achieve low dielectric electrical specifications while improving the fluidity and glass transition temperature of the resin composition, the following is a special example.
[0049] Preparation of the second resin
[0050] A low molecular weight polyphenylene ether resin material with a number average molecular weight (Mn) of less than or equal to 12,000 or less than or equal to 10,000 (for example, Mn = 500, 1400, 1600 or 1800) is dissolved in dimethylacetamide, followed by the addition of potassium carbonate and tetrafluoronitrobenzene. The above reaction solution is heated to 140°C and reacted for 8 hours, then cooled to room temperature, and then filtered to remove the solid. Methanol / water is used to precipitate the filtrate, and the precipitate is the nitrated polyphenylene ether resin. After the nitrated polyphenylene ether resin is dissolved in dimethylacetamide, it is hydrogenated at 90°C for 8 hours to obtain an aminated polyphenylene ether resin. The aminated polyphenylene ether resin is then placed in toluene, and maleic anhydride and p-toluenesulfonic acid are added thereto, and the temperature is raised to 120 degrees and refluxed, and the reaction is performed for 8 hours to obtain a second resin. It is a polyphenylene ether resin (PPE-BMI) modified with bismaleimide.
[0051] Preparation of resin composition
[0052] The resin composition shown in Table 1 was mixed with toluene to form a varnish of a thermosetting resin composition. The varnish was impregnated with Nan Ya fiberglass cloth (Nan Ya Plastics Co., Ltd., cloth type 1078LD) at room temperature, and then dried at 170°C (impregnation machine) for several minutes to obtain a prepreg with a resin content of 79% by weight. Finally, 4 prepregs were stacked between two 35μm thick copper foils, and kept at a constant temperature for 20 minutes at a pressure of 25kg / cm2 and a temperature of 85°C. Then, the temperature was increased to 210°C at a heating rate of 3°C / min, and the temperature was maintained at a constant temperature for 120 minutes. Then, it was slowly cooled to 130°C to obtain a 0.59mm thick copper foil substrate, and various properties were evaluated.
[0053] Evaluation Methodology
[0054] The copper foil substrates prepared in each example and comparative example were evaluated according to the following method. The results are shown in Table 1.
[0055] The glass transition temperature (°C) was measured by dynamic mechanical analyzer (DMA).
[0056] Water absorption (%): The sample was heated in a pressure cooker at 120°C and 2 atm for 120 minutes, and the weight change before and after heating was calculated.
[0057] 288℃ solder resistance (seconds): The sample is heated in a 120℃ and 2atm pressure cooker for 120 minutes and then immersed in a 288℃ solder furnace. The time required for the sample to explode and delaminate is recorded.
[0058] Dielectric constant Dk: The dielectric constant Dk was measured at a frequency of 10 GHz using a dielectric analyzer (HP Agilent E4991A).
[0059] Dissipation factor Df: The dielectric loss Df at a frequency of 10 GHz was measured using a dielectric analyzer (HP Agilent E4991A).
[0060] Resin flow rate: Press at 170°C ± 2.8°C with 200 ± 25 PSI for 10 minutes. After melting and cooling, punch out the disc, weigh the disc accurately, and calculate the resin outflow.
[0061] Resin phase separation (section analysis):
[0062] Step 1: Cut the copper foil substrate into 1cm*1cm size and place it into the mold for resin grouting.
[0063] Step 2: After the resin is completely dried and hardened, grind and polish the sample.
[0064] Step 3: Use a high-resolution microscope such as OM / SEM to analyze the sample and confirm whether there is resin phase separation inside the sample.
[0065] In Table 1, the detailed information of each component is as follows:
[0066] First resin: LDM-03 (purchased from Denka)
[0067] Second resin: Use the prepared second resin
[0068] SBS resin: 1,2-SBS Type-C (purchased from Japan Soda Co., Ltd.)
[0069] Crosslinking agent DVB: divinylbenzene crosslinking agent
[0070] Crosslinking agent TAIC: Triallyl isocyanuric acid crosslinking agent
[0071] Halogen-free flame retardant: PQ-60 (purchased from Jinyi Chemical Company)
[0072] Silica: EQ2410-SMC (purchased from Sanshiki Company)
[0073] Peroxide: Luperox F (purchased from ARKEMA)
[0074] Siloxane coupling agent: Z-6030 (purchased from Dow Corning)
[0075] Table 1. Composition and property evaluation of the resin compositions of Comparative Examples 1 to 3 and Examples 1 to 3
[0076]
[0077] In Table 1, Comparative Examples 1 to 3 use triallyl isocyanuric acid (TAIC) as a crosslinking agent, while Examples 1 to 3 use divinylbenzene (DVB) as a crosslinking agent. The results show that compared to Comparative Examples 1 to 3 using TAIC crosslinking agent, Examples 1 to 3 using DVB crosslinking agent (Example 1 compared to Comparative Example 1, Example 2 compared to Comparative Example 2, Example 3 compared to Comparative Example 3) can increase the glass transition temperature, improve the resin fluidity, and reduce the loss factor (Df) while maintaining similar low dielectric electrical specifications.
[0078] In summary, the resin composition of the present invention can achieve low dielectric electrical specifications (e.g., low dielectric constant, low dissipation factor) by combining a first resin (formed by polymerization of a monomer mixture including styrene, divinylbenzene and ethylene) with a second resin (including a polyphenylene ether resin modified with bismaleimide). In addition, by introducing a cross-linking agent containing divinylbenzene, the glass transition temperature can be increased while maintaining the electrical properties of the substrate and the fluidity can be improved, thereby improving the overall processability.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A resin composition, characterized in that: include: Resin base, comprising: A first resin is formed by polymerizing a first monomer mixture including styrene, divinylbenzene and ethylene; The second resin includes a polyphenylene ether resin modified with bismaleimide; and Divinylbenzene crosslinker; Halogen-free flame retardant Spherical silica; and Siloxane coupling agent.
2. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the resin base, the content of the first resin is 30 parts by weight to 60 parts by weight, the content of the second resin is 20 parts by weight to 40 parts by weight, and the content of the divinylbenzene crosslinking agent is 10 parts by weight to 30 parts by weight.
3. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the resin base, the added amount of the halogen-free flame retardant is 20 phr to 50 phr.
4. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total weight of the resin base and the halogen-free flame retardant, the added amount of the spherical silica is 20 parts by weight to 50 parts by weight.
5. The resin composition according to claim 1, characterized in that The molar ratio of styrene:divinylbenzene:ethylene in the first monomer mixture is 1:1:1 to 2:2:
1.
6. The resin composition according to claim 1, characterized in that The number average molecular weight of the first resin is 4,500 to 6,500.
7. The resin composition according to claim 1, characterized in that The resin substrate further comprises: SBS resin is polymerized from a second monomer mixture including styrene, 1,2-butadiene and 1,4-butadiene.
8. The resin composition according to claim 7, characterized in that The molar ratio of styrene:1,2-butadiene:1,4-butadiene in the second monomer mixture is 1:6:4 to 4:9:
3.
9. The resin composition according to claim 7, characterized in that Based on 100 parts by weight of the resin base, the content of the SBS resin is 0 parts by weight to 30 parts by weight.
10. The resin composition according to claim 7, characterized in that The weight average molecular weight of the SBS resin is 3500 to 5500.
11. The resin composition according to claim 1, characterized in that The spherical silica has a surface modification of acrylic or vinyl and has an average particle size of 2.0 micrometers to 3.0 micrometers.
12. The resin composition according to claim 1, characterized in that The electrical properties of the resin composition are a dielectric constant of 3.0 to 3.1 and a loss factor of less than 0.0015, and a heat resistance specification of a glass transition temperature greater than 210°C.
